Increasing Production Target Thorough Major Maintenance - Muhammad Rifqi Aurynnanda Adinugraha (Citakonsultindo, 2024)
Suboptimal production equipment conditions hinder optimal production activities, necessitating maintenance to maintain production performance. RU VI Balongan has decided to renew several important units to not only improve production capability but also to increase it, enabling the achievement of production targets to meet demand. The Major Turn Around project conducted in 2022 focused on this aspect, where revamping activities were carried out on two main processing units, namely the Crude Distillation Unit (CDU), and the Residue Catalytic Cracking (RCC) unit was replaced. This Turn Around project is also one of the efforts to achieve the RDMP (Refinery Development Master Plan) as one of the National Strategic Projects (PSN), where RU VI aims to increase the total production capacity from 125,000 barrels/day to 150,000 barrels/day. PT Pertamina International Refinery RU VI Balongan is one of the 6 processing units owned by PT Pertamina (Persero) engaged in the production of fuels, non-fuels, and petrochemicals.